Quantum recentivism - Czerny, Janusz (Folia Philosophica, 2003)
The author of the present article has striven to prove the existence of an analogy between the ideological and theoretical premises of quantum mechanics and the theses of recentivist theory. Quantum physics deals with single physical facts which in science are called the undulant function. It turns out that recentivism is based on the anthropological premises embedded in the context of “here-now-being”. This means the acceptance of a reductionist attitude in both quantum theory and recentivism. The author has adduced in the article a number of arguments which confirm the correspondence between the research methods of quantum physics and the premises of recentivism.